2015
DOI: 10.1016/j.schres.2015.03.033
|View full text |Cite
|
Sign up to set email alerts
|

Determinants of different aspects of everyday outcome in schizophrenia: The roles of negative symptoms, cognition, and functional capacity

Abstract: Cognition, negative symptoms, and depression are potential predictors of disability in schizophrenia. We present analyses of pooled data from four separate studies (all n>169; total n=821) that assessed differential aspects of disability and their potential determinants. We hypothesized that negative symptoms would predict social outcomes, but not vocational functioning or everyday activities and that cognition and functional capacity would predict vocational functioning and everyday activities but not social … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

9
113
2
1

Year Published

2016
2016
2022
2022

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(125 citation statements)
references
References 45 publications
9
113
2
1
Order By: Relevance
“…Even after restricting the calculation of negative symptom duration by removing N1-Social Anhedonia, long-term negative symptoms were still adversely related to social functioning. This pattern is consistent with previous findings in adult patients with an established course of illness that have shown that negative symptoms are more related to social functioning than other aspects of everyday functional outcome (i.e., vocational outcomes), even when accounting for neurocognitive impairments (Leifker et al, 2009; Strassnig et al, 2015). Moreover, past findings from our group have shown that neurocognitive abilities are strongly related to role functioning at outcome, in particular verbal memory deficits (Carrión et al, 2013), further suggesting that certain deficits may be differentially related to specific domains of functioning at outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Even after restricting the calculation of negative symptom duration by removing N1-Social Anhedonia, long-term negative symptoms were still adversely related to social functioning. This pattern is consistent with previous findings in adult patients with an established course of illness that have shown that negative symptoms are more related to social functioning than other aspects of everyday functional outcome (i.e., vocational outcomes), even when accounting for neurocognitive impairments (Leifker et al, 2009; Strassnig et al, 2015). Moreover, past findings from our group have shown that neurocognitive abilities are strongly related to role functioning at outcome, in particular verbal memory deficits (Carrión et al, 2013), further suggesting that certain deficits may be differentially related to specific domains of functioning at outcome.…”
Section: Discussionsupporting
confidence: 92%
“…Exploration of different domains of functioning is important as these may be differentially affected and deficits may be driven by different aspects of illness (Strassnig et al, 2015). Recent evidence in the UHR group suggests social and occupational functioning are dissociable domains that are not always correlated with one another (Cornblatt et al, 2007;Cotter et al, 2014Cotter et al, , 2015b.…”
Section: Strengths and Limitationsmentioning
confidence: 99%
“…In another meta-analysis of 8 RCTs ( n = 452) in schizophrenia, memantine improved cognition compared to placebo, with a weighted MD of 3.09 ( p < 0.00001) [43]. Improvements in negative symptoms, which are associated with functioning [44, 45], have also been shown with memantine. However, these findings should be taken with caution, as negative symptoms were measured with the Scale for the Assessment of Negative Symptoms (SANS), the Positive and Negative Syndrome Scale (PANSS), and the Brief Psychiatric Rating Scale (BPRS), which do not differentiate primary versus secondary negative symptoms, instead of the Schedule for the Deficit Syndrome [46], which does differentiate these symptoms.…”
Section: Introductionmentioning
confidence: 99%